INDOFOOD'S GLOBAL STRATEGY: BALANCING INNOVATION, SUSTAINABILITY, AND MARKET EXPANSION - Sihombing, Jonathan Debson; Pratomo, Luki (Jurnal Ekonomi Trisakti, 2024)
Indofood as a prominent Indonesian food and beverage corporation, occupies a significant position in the global market. This paper investigates Indofood's competitive stance within the industry through a TOWS matrix analysis, which evaluates the company's external opportunities and threats, internal strengths and weaknesses. Indofood's adaptability to dynamic market conditions has been pivotal in sustaining its competitive edge worldwide, particularly in the instant noodles sector. The study aims to provide a comprehensive overview of Indofood's status as a global leader in this domain, utilizing relevant academic theories and frameworks. The findings indicate that Indofood has adeptly navigated its operational environment, effectively managing buyer power through fostering strong brand loyalty and addressing supplier relationships with strategic solutions. Additionally, Indofood's strategic product development and diversification efforts underscore its commitment to expanding its product portfolio and business operations. Following a product recall, it is recommended that Indofood fortifies its safety protocols and communicates transparently about the measures taken to ensure consumer safety.